THE USE OF LASER TECHNOLOGIES IN DENTISTRY - Abduraxmonova, Shohista (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
This article discusses the application of laser technologies in modern dentistry and their role in improving diagnostic and therapeutic outcomes. The use of lasers has revolutionized dental practice by enabling minimally invasive, precise, and painless procedures. The article examines various types of dental lasers, including diode, erbium, and CO₂ lasers, and their specific uses in soft and hard tissue treatments. It also highlights the advantages of laser therapy, such as reduced bleeding, faster healing, sterilization of the operative field, and improved patient comfort. Furthermore, safety aspects and limitations of laser use in dental practice are analyzed.